2020
DOI: 10.3389/fphys.2020.00681
|View full text |Cite
|
Sign up to set email alerts
|

The Commonalities and Differences in Mitochondrial Dysfunction Between ex vivo and in vivo Myocardial Global Ischemia Rat Heart Models: Implications for Donation After Circulatory Death Research

Abstract: Quader et al. Mitochondrial Dysfunction in DCD Hearts found differential mitochondrial damage between the in vivo ischemia and the ex vivo ischemia setup. Therefore, consideration should be given to the mode of ischemia while evaluating and testing myocardial protective interventions targeting mitochondria to reduce IR injury in hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
(96 reference statements)
0
11
0
Order By: Relevance
“…Besides, hypoxic pulmonary vasoconstriction following asphyxiation results in right ventricular dilatation and more damage to hearts compared with exsanguination (3,31). To induce asphyxiation, Quader et al terminated the ventilation support following paralyzing skeletal muscles with muscle relaxants (32,33), while Tolboom et al chose to transect the diaphragm (12,13). Asphyxiation can also be induced by tracheal clamping or by median sternotomy and opening the pleurae (14,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, hypoxic pulmonary vasoconstriction following asphyxiation results in right ventricular dilatation and more damage to hearts compared with exsanguination (3,31). To induce asphyxiation, Quader et al terminated the ventilation support following paralyzing skeletal muscles with muscle relaxants (32,33), while Tolboom et al chose to transect the diaphragm (12,13). Asphyxiation can also be induced by tracheal clamping or by median sternotomy and opening the pleurae (14,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no pre-mortem interventions are allowed in DCD hearts due to socio-ethical reasons [38]. Since warm ischemia is inevitable with the DCD process, damage to mitochondria is already established in these hearts [19]. A recent study showed that mitochondrial transplantation decreased cardiac injury in rabbit hearts following in vivo ischemia-reperfusion injury by improving mitochondrial function [39].…”
Section: Plos Onementioning
confidence: 99%
“…Most of the knowledge on the series of events and on the extent of damage to the mitochondria in the ischemic or reperfused hearts comes from exvivo ischemia studies [15][16][17][18]. A recent study showed that the DCD process (in vivo ischemia) leads to mitochondrial dysfunction similar to the ex vivo studies but with distinct differences [19]. In this study we will address the changes in mitochondrial and cardiac function from DCD hearts subjected to different periods of in vivo ischemia and in vitro reperfusion.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, not all protocols employ the same definition of the start of warm ischemia. For example, some measure cardiac asystole by electrocardiogram ( 11 ) while others define the beginning of ischemia when the peak systolic pressure drops below 30 mmHg or asystole ( 12 , 13 ), or when the blood pressure was non-pulsatile or the mean arterial pressure less than 30 mmHg ( 14 , 17 ). As such, strict comparison among varying pre-clinical models requires careful interpretation, but when possible, it may aid in advancing our understanding of the pathophysiologic processes involved.…”
Section: Introductionmentioning
confidence: 99%
“…The consideration of this pre-ischemic phase and the simulation of the DCD process in a donor is receiving more and more attention in the field, and several in-situ rat models have recently been developed (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, no standard protocol is available; for example, initiation of the DCD process can be simulated in different ways; by simply terminating the ventilatory support (14,15,17), by terminating ventilatory support in combination with a tracheal clamp (12,13), with or without the addition of respiratory muscle paralysis (11,16), or by the transection of the diaphragm (19,20). Furthermore, not all protocols employ the same definition of the start of warm ischemia.…”
Section: Introductionmentioning
confidence: 99%